Association Between NT-proBNP and Prolonged Length of Stay in Hospital Among Preterm Infants Born at 28–31 Weeks' Gestation - Ge, Jian; Luo, Chenghan; Lei, Mengyuan; Shi, Zanyang; Cheng, Xinru; Zhao, Min; Zhao, Yanting; Song, Min; Ding, Wenqian; Wang, Mengmeng; Cao, Wenjun; Mao, Fengxia; et al. (Frontiers in Pediatrics, 2022)
Objective: In early life of preterm infants, the relationship between heart function and length of hospitalization is unclear. This study aims to examine the association between serum NT-proBNP level on the 7th day (NT-proBNP7) after born and length of hospitalization among preterm infants. Methods: A retrospective cohort study was conducted. Patients included 709 preterm infants born at 28 to 31 weeks' gestational age (GA) admitted to NICU of the First Affiliated Hospital of Zhengzhou University between December 20, 2016, to April 31, 2021. Main outcome: late discharge (postmenstrual age at discharge was in the fourth quartile (highest) among infants born at the same GA). Exposure factor: NT-proBNP7. Results: We observed increased prevalence ratios for late discharge among the tertile of logarithm of NT-proBNP7 level (LnNT-proBNP7) was positive. Compared with the lowest tertile, infants in the highest tertile of LnNT-proBNP7 had an 8.4-fold increased probability of late discharge, and the results were consistent for the subgroups. Next, a nonlinear (S-shaped) relationship between LnNT-proBNP7 and late discharge was observed, whose turning points were 7.5 and 9. The effect sizes and the confidence intervals on the left of the first turning point, between two turning points and on the right of the second turning point were 0.6 (95% CI, 0.2- 1.6), 5.0 (95% CI, 2.4- 10.6) and 1.1 (95% CI, 0.2- 6.1), respectively. In addition, the prevalence of BPD, NEC, nosocomial infection or any of them were highest in the group of LnNT-proBNP7 ≥9, lowest in the group of LnNT-proBNP7 <7.5. Conclusion: Higher NT-proBNP7 levels were associated with longer hospitalization. The relationship between LnNT-proBNP7 and late discharge was S-shaped. LnNT-proBNP7 was positively related with late discharge when LnNT-proBNP7 was between 7.5 and 9.